2020
DOI: 10.1590/1678-5150-pvb-6172
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic morphological aspects, ecometry and rebound tonometry of the eye bulb in sloth (Bradypus variegatus)

Abstract: The field related to the visual system of wild animals is deeply scarce. Settling anatomical and physiological parameters for these animals is still a descriptive vision for Bradypus variegatus (Schinz, 1825). Thus, our research aimed to determine patterns of normal eye for this species. For this purpose, eight eye bulbs were dissected from the carcasses obtained by natural death, and then performed an overview of ocular anatomical. Rebound tonometry (RBT) and ocular B-mode ultrasonography were also applied fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
(70 reference statements)
2
4
0
Order By: Relevance
“…Although examined group of animals in our study were small, the obtained results of the eyeball macroscopic measurements were higher or similar to the results of the brown-throated sloth where there is a special microenvironment for their renewal and proliferation (Sanchez & Daniels, 2016). Macroscopically, the tapetum lucidum in the southern two-toed sloth was not identified, as was the case with Bradypus variegatus (Braz et al, 2020;Sena et al, 2021), while our histological studies showed the presence of choroidal tapetum lucidum cellulosum, the cells of this latter being characterized by folding of the cell membrane and irregular layering. Such structure of tapetum lucidum proves its degeneration, which was similarly demonstrated in the Asiatic black bear (Ursus thibetanus; Paszta et al, 2022) and ranch mink (Mustela vision; Braekevelt, 1989;Ollivier et al, 2004).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Although examined group of animals in our study were small, the obtained results of the eyeball macroscopic measurements were higher or similar to the results of the brown-throated sloth where there is a special microenvironment for their renewal and proliferation (Sanchez & Daniels, 2016). Macroscopically, the tapetum lucidum in the southern two-toed sloth was not identified, as was the case with Bradypus variegatus (Braz et al, 2020;Sena et al, 2021), while our histological studies showed the presence of choroidal tapetum lucidum cellulosum, the cells of this latter being characterized by folding of the cell membrane and irregular layering. Such structure of tapetum lucidum proves its degeneration, which was similarly demonstrated in the Asiatic black bear (Ursus thibetanus; Paszta et al, 2022) and ranch mink (Mustela vision; Braekevelt, 1989;Ollivier et al, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…Bradypus variegatus;Braz et al, 2020) and the pale-throated sloth (Bradypus tridactylus;Hayssen, 2009). Histological studies revealed that the cornea in the examined southern two-toed sloth consists of only four layers (no Bowman's membrane) similar to Watillon and Goffmanni's research on Choloepus hoffmanniF I G U R E 5 Photomicrograph of the histochemistry of southern two-toed sloth upper and lower eyelids.…”
mentioning
confidence: 61%
See 3 more Smart Citations